Analisis Kepuasan Pasien Terhadap Layanan Konsultasi Kesehatan Digital: Perspektif Generasi Milenial Di Kota Kendari - Jumakil (STIKES Columbia Asia Medan, 2025)
Background: The millennial generation, born between 1981 and 1996, is the demographic group most adaptable to digital technology. As digital natives, this generation tends to be more open and familiar with the use of technology in various daily life activities, including accessing health services. Method: This type of research is quantitative research, and is an explanatory research. Sampling uses accidental sampling techniques. The number of samples is 300 millennials. Result: a positive and significant influence of System Quality on satisfaction in digital health service consultations with an original sample value of 0.599 and a p-value of 0.000 <0.05. Information Quality on satisfaction in digital health service consultations with an original sample value of 0.226 and a p-value of 0.001 <0.05. and Service Quality on satisfaction in digital health service consultations with an original sample value of 0.160 and a p-value of 0.003 <0.05. Conclusion: Millennials' satisfaction with digital health services is determined by system quality, service quality, and information quality.